2013
DOI: 10.1002/pon.3340
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial screening effects on health‐related outcomes in patients receiving radiotherapy. A cluster randomised controlled trial

Abstract: Our results suggest that the use of a psychosocial screening instrument among patients receiving radiotherapy in itself does not sufficiently improve patients' health-related outcome. The effective delivery of psychosocial care depends upon several components such as identification of distress and successful implementation of screening procedures. One of the challenges is to get insight in the effects of early referral of cancer patients for psychosocial support because early referral might have a favourable e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 53 publications
4
15
0
1
Order By: Relevance
“…This finding is in line with other (nurse) intervention studies with the DT . Albeit, they used the DT in a different way and with a shorter follow‐up period . In this study, 20% to 49% of the patients experienced distress (DT ≥ 5) at one or more time‐points.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is in line with other (nurse) intervention studies with the DT . Albeit, they used the DT in a different way and with a shorter follow‐up period . In this study, 20% to 49% of the patients experienced distress (DT ≥ 5) at one or more time‐points.…”
Section: Discussionsupporting
confidence: 89%
“…The main result is that using the DT by a nurse at regular time‐points did not improve global QOL 2 years after the end of treatment. This finding is in line with other (nurse) intervention studies with the DT . Albeit, they used the DT in a different way and with a shorter follow‐up period .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Rahn et al [47] studied 523 breast cancer patients undergoing RT as a part of breast conservation and estimated 40% anxiety prior to RT, which declined over time. A Dutch cluster randomized trial by Braeken et al [67] with 568 general RT patients identified 21% anxiety, 7% depression, and 39% distress at 3 months following RT completion and concluded that distress screening alone does not alleviate psychosocial function decline. A recently reported (abstract-only) multi-institutional trial performed by the RT Oncology Group (RTOG 0841) of 455 general RT patients assessed at a single point prior to RT reported a 16.5% prevalence rate of depressive symptoms using the DT and other rapid instruments [4].…”
Section: Instrumentsmentioning
confidence: 99%
“…Standardized and internationally validated instruments are available to assess psychosocial distress [8]. However, recently published results showed that early detection of distress and referral to psychosocial care does not automatically show a positive effect on a patient's quality of life and therefore should be embedded in a stepped-care program [9]. The stepped-care model comprises systematic identification of needs, integrated delivery of psychosocial care by care managers ranging from counseling to individual psychotherapy, and appropriate specialist supervision.…”
Section: Rationale Of Psychosocial Care For Cancer Patientsmentioning
confidence: 99%